Social vs traditional media communication: brand origin associations strike a chord. Issue 1 (5th December 2017) - Morra, Maria Cristina; Ceruti, Francesca; Chierici, Roberto; Di Gregorio, Angelo
Abstract : Purpose: The purpose of this study is to develop an analytical comparison between the impact of social media communication (both user-generated and firm-created) and the effects of traditional media communication. In particular, the components of customer-based brand equity and any difference in the effects according to brand origin associations are investigated. The target group consisted of fans and followers of beer brands on social media. Design/methodology/approach: In all, 192 questionnaires were collected a survey link that was posted on beer brand pages that operate in the Italian market. Structural equation modeling was developed to investigate the impact of social and traditional media communication on brand equity and a multi-group analysis to examine the differences according to the brand names' origin associations. Findings: Results show that fans and followers cannot be considered as a collective unit. Additionally, consumers make a clear distinction between firm-created/user-generated social media and traditional media communication. Specifically, they distinguish how the effects of the two media outlets differ in relation to the brand origin associations. International brands should concentrate on both firm-created and user-generated communication, whereas national (Italian) brands should foster their firm-created communications. In both cases, however, traditional media communication loses its effectiveness on the brand equity components. Originality/value: Contrary to existing literature, this project compares the effect of 2.0 and traditional media on various social media platforms, pointing out two different models according to the brands' origin associations. This study develops interesting insights both for international companies with huge brand portfolios and for national firms in a complex market like those for beer.